The effect of inhaling mercury (Hg) on the hepar cells and the role of green tea extract as antioxidant - Afriza, Dhona (Padjadjaran Journal of Dentistry, 2011)
This research aimed to identify the effect of inhaling mercury on the hepar cells of white mice and the role of green tea extract as an antioxidant on such hepar cells having exposed to mercury histopathologically. It was an experimental research by using 48 male white mice (Mus musculus) as the sample. The sample was divided into 8 groups i.e.: A, B, C, and D, which were given treatment for 3 and 6 weeks. Each group consisted of 6 mice. A group was a negative control which did not get any treatment. Group B as a positive control group was exposed to mercury. Group C was exposed to mercury and was given green tea extract at dosage 0.52 mg/20 gr of body weight. Group D was exposed by mercury and was given green tea extract at dosage 1.04 mg/ 20 gr of body weight. All white mice in the group B, C, and D were exposed to mercury through inhalation for 4 hours daily. To identified the effect of mercury, the hepar cells in all 4 groups were examined at the 3rd and 6th week by making histopathologic preparation in the Histopathology Laboratory Faculty of Medicine Universitas Andalas. Then, the preparation was examined through Binocular Light Microscope in ordered to see the deficient occurred. The data obtained were analyzed by ANOVA method and independent T-test with confidence level = 95%. It was revealed that the hepar cells that were being exposed to mercury regularly were being degenerates. Then, the amount of green tea extract given reduces the degeneration occurred.